The first Americans : the Pleistocene colonization of the New World - Jablonski, Nina G. (Memoirs of the California Academy of Sciences, 2002)
As modern humans spread around the globe, the Americas represented the final continental frontier. These first colonists were modern in appearance and technology, but who were they and when did they arrive? Traditional answers to these questions have come under increasing scrutiny in the face of new findings from artifacts, skeletal remains, genes, and languages. The peopling of the Americas has become one of archeology's most compelling and contentious subjects, as these new lines of inquiry and evidence reveal a more complex picture. In The First Americans: The Pleistocene Colonization of the New World, distinguished scientists from the fields of archeology, physical anthropology, paleoecology, genetics, and linguistics assess the latest evidence from Siberia to Chile and other provocative ideas for how, when, and where humans entered the Americas.